Motivational counselling and SMS-reminders for reduction of daily sitting time in patients with rheumatoid arthritis: a descriptive randomised controlled feasibility study. Issue 1 (December 2016) - Thomsen, T.; Aadahl, M.; Beyer, N.; Hetland, M.; Løppenthin, K.; Midtgaard, J.; Christensen, R.; Esbensen, B.
Abstract Background Patients with rheumatoid arthritis (RA) spend a high proportion of their waking time in sedentary behaviour (SB) and have an increased risk of cardiovascular disease. Reduction of SB and increase in light intensity physical activity has been suggested as a means of improvement of health in patients with mobility problems. Short-term intervention studies have demonstrated that SB can be reduced by behavioural interventions in sedentary populations. To evaluate descriptively the feasibility of recruitment, randomisation, outcome assessments, retention and the acceptability of an individually tailored, theory-based behavioural intervention targeting reduction in daily sitting time in patients with RA. Methods A randomised, controlled trial with two parallel groups. RA patients >18 years of age and Health Assessment Questionnaire (HAQ) score < 2.5 were consecutively invited and screened for daily leisure time sitting > 4 h. The 16-week intervention included 1) three individual motivational counselling sessions and 2) individual text message reminders aimed at reducing daily sitting time. The control group was encouraged to maintain their usual lifestyles. Outcomes were assessed at baseline and after the 16 week intervention. Daily sitting time was measured using an ActivPAL3TM activity monitor. The study was not powered to show superiority; rather the objective was to focus on acceptability among patients and clinical health professionals. Results In total, 107 patients were invited and screened before 20 met eligibility criteria and consented; reasons for declining study participation were mostly flares, lack of time and co-morbidities. One patient from the control group dropped out before end of intervention (due to a RA flare). Intervention participants completed all counselling sessions. All procedures regarding implementation of the trial protocol were feasible. The daily sitting time was reduced on average by 0.30 h in the intervention group unlike the control group that tended to increase it by 0.15 h after 16 weeks. Conclusions This study shows that an individually tailored behavioural intervention targeting reduction of SB was feasible and acceptable to patients with RA. Trial registration The Danish Data Protection Agency (ref.nb. 711-1-08 - 20 March 2011), the Ethics Committee of the Capital Region of Denmark (ref.nb. H-2-2012-112- 17 October 2012), clinicaltrials.gov (NCT01969604 - October 17 2013, retrospectively registered).